2010
DOI: 10.1016/j.acuro.2010.02.043
|View full text |Cite
|
Sign up to set email alerts
|

Tumor neuroendocrino primario del riñón

Abstract: Varias modalidades terapéuticas han sido propuestas en la literatura para solucionar la obstrucció n y el fracaso renal. Posicionar a la paciente en decú bito lateral puede mejorar la descompresió n del uréter afectado; asimismo, una amniotomía podría hacerse para aliviar la obstrucció n y mejorar la funció n renal, sobre todo en caso de polihidramnios. Pero actualmente, la colocació n de nefrostomías percutá neas o catéteres ureterales (si el reimplante lo permite) con control ecográ fico se ha convertido en … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Metastatic renal carcinoid has been noted to be resistant to chemotherapy [36, 83]. Studies with single agent therapy with 5FU, cisplatin and doxorubicin have been shown to have a response rate of approximately 20%, and combination chemotherapy does not seem to be significantly superior to single agents in the treatment of metastatic carcinoids [84].…”
Section: Discussionmentioning
confidence: 99%
“…Metastatic renal carcinoid has been noted to be resistant to chemotherapy [36, 83]. Studies with single agent therapy with 5FU, cisplatin and doxorubicin have been shown to have a response rate of approximately 20%, and combination chemotherapy does not seem to be significantly superior to single agents in the treatment of metastatic carcinoids [84].…”
Section: Discussionmentioning
confidence: 99%